Intrabeam Radiation Inhibits Proliferation, Migration, and Invasiveness and Promotes Apoptosis of MCF-7 Breast Cancer Cells. (19th July 2019) - Pan, Lingxiao; Wan, Minghui; Zheng, Wenbo; Wu, Rui; Tang, Wei; Zhang, Xiaoshen; Yang, Tong; Ye, Changsheng
Intraoperative radiotherapy differs from the more commonly used external beam radiation with respect to fractionation, radiation energy, dose rate, and target volume, which may influence the irradiated cells in a complex manner. However, experimental studies of intraoperative radiotherapy are limited. Intrabeam is a frequently used intraoperative radiotherapy device; we evaluated its effects on the proliferation, apoptosis, migration, and invasion of MCF-7 human breast cancer cells. We performed colony formation assays for cells irradiated with single radiation doses of 0 to 16 Gy. Other cells were irradiated with single radiation doses of 0 to 6 Gy and then continued to be cultured. We measured cell-cycle distributions and apoptosis rates 24 hours later, using flow cytometry, and performed wound-healing assays, Transwell tests, and terminal deoxynucleotidyl transferase–mediated 2′-deoxyuridine 5′-triphosphate nick-end labeling staining 4 weeks later. Colony formation assays showed no positive colonies from cells irradiated with doses of ≥6 Gy. In flow cytometry, the experimental groups had higher late-apoptosis/necrosis rates ( P < .01) and higher percentages of cells arrested in G1 phase ( P < .01). Experimental groups also had much lower scratch-repair rates in the wound healing assay ( P < .001) and higher apoptosis rates in the terminal deoxynucleotidyl transferase–mediated 2′-deoxyuridine 5′-triphosphate nick-end labeling assay ( P < .05). In Transwell tests, the 4 Gy and 6 Gy groups had fewer invading cells than the control group ( P < .05). Single-dose irradiation of 6 Gy with the Intrabeam device can effectively inhibit proliferation, migration, and invasiveness and promote apoptosis in MCF-7 cells with long-lasting effects.